Factores de riesgo para la infección del tracto urinario en gestantes del Hospital Hermilio Valdizán de Huánuco - Randhu Cuba, Percy Agüero (2018)
Introduction: The objective of the present study was to determine the relationship of the factors related to burnout syndrome in health staff Hermilio Valdizán Regional Hospital in the period 2014. Methods: The study analyzed from patients treated from January to December 2010, it was developed an observational, analytical, transversal, retrospective case – control study, of 130 patients: 65 cases and 65 controls which were chosen at randomized from the record of the department of Gynecology, cases were those pregnant patients with diagnosis with urinary tract infection and controls were those pregnant patients who assisted during this period for various reasons without a diagnosis of urinary tract infection; information gathering was to review the medical records taken as a reference sheet prenatal care, the base characteristics of the groups were compared using chi-square test. It was estimated the association between the two groups and risk factors by the odds ratio (OR) it was estimated using the test bivariate associations T. Results: The pregnant adolescents 11 to 19 years old are more likely than pregnant women aged 20 years old or more to present urinary tract infection (OR: 2,81) (95% CI 1,20 to 6,56), the presence of anemia was also associated with increased risk of urinary tract infection (OR 2,72) (95% CI 1,08 to 6,83), and the primigestacion (OR:3) (CI: 95% 1,45 to 6,20). Conclusions: Urinary tract infection in pregnant women was associated with the primigestacion, adolescence and the presence of anemia.